PERAN VIDEO EDITOR DALAM PRODUKSI WINNING CONTENT INSTAGRAM @MCH.ID_OFFICIAL DI WILL&DO BUSINESS PARTNER - Nurwahyudin; Hari Otang Sasmita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of social media has increased the use of short-form video content as a medium for digital communication and promotion. In this process, video editors play an important role in packaging messages to make them more engaging and capable of increasing audience interaction. However, studies discussing the role of video editors in creating winning content on social media remain limited, particularly regarding content production processes within a creative agency environment. This study aims to analyze the role of video editors in producing winning content for the Instagram account @MCH.id_official, describe the content production and editing workflow, and identify the challenges encountered during the production process. This research employed a descriptive qualitative approach with data collected through observation, active participation, interviews, documentation, and literature studies. The main informant was the Creative Production Manager of Will&Do Business Partner. The findings indicate that video editors are involved in various stages of content production, including timeline arrangement through the cut-to-cut technique, color correction and color grading, keyframe adjustment, subtitle creation, text element and graphic element insertion, as well as the addition of sound effects and background music. The study also found that talking head content supported by subtitles, text elements, and visual movements such as zoom in and zoom out tends to generate higher audience engagement. In addition, the first 5–15 seconds of a video were identified as a crucial factor in retaining audience attention. The main challenge faced by the editor was the placement of text element layouts, which required more time than other editing stages. The findings suggest that the role of a video editor extends beyond technical editing skills and contributes significantly to the creation of winning content on the Instagram platform.